ANATOMI DAUN PIPERACEAE DARI KAWASAN GUNUNG SLAMET, JAWA TENGAH - Fatmawati Tihurua, Eka; Puji Astuti, Inggit; Ridho Witono, Joko (Center for Plant Conservation Bogor Botanic Garden, Indonesian Institute of Sciences, 2011)
Leaf anatomy of Piperaceae from Gunung Slamet, Central Java has made with standardÂ paraffin and paradermal method. The results showed that Piperaceae has dorsiventral leaf, hypostomatatic or amphistomatatic, tetracytic and cyclocytic stomata type. Hypoderm tissue exist in upper and/or lower part of leaf, mesophyll was arranged by 1-2 layers of palisade and 2-7 layers of sponge tissue. There were 3 types of trichome i.e. glandular trichome which had globose cell with short stalk, bicellular glandular trichome and multicellular & uniseriate non-glandular trichome. The shape of the crystal of Piperaceae from gunung Slamet are sand, needle, drusse or prismatic which distributed in hypodermis, mesophyll and midrib. Piperaceae petiole was arranged by open or sometimes closed circle vascular bundles. These open vascular bundles were crescent shape or resemble to U and V shapes.Â